2021
DOI: 10.1097/01.aoa.0000796164.39941.ec
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Psychological and Physical Outcomes of Women After Postdural Puncture Headache: A Retrospective, Cohort Study

Abstract: U mbilical cord prolapse is an emergency with risk for significant complications, including prematurity and birth asphyxia. As cord compression and umbilical arterial vasospasm can lead to fetal hypoxia and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…Many studies have begun to focus on long‐term sequalae of women with PDPH including chronic backache and headache 4,6,11,21 . We did not find a difference between the two groups in terms of long‐term pain; again, our study was not powered for this analysis and this was just an exploratory outcome.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Many studies have begun to focus on long‐term sequalae of women with PDPH including chronic backache and headache 4,6,11,21 . We did not find a difference between the two groups in terms of long‐term pain; again, our study was not powered for this analysis and this was just an exploratory outcome.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, as a secondary analysis of a previously performed and part of a quality improvement program, we had data on chronic headache and backache in these women 11 . This was evaluated by a telephone interview made at least 6 months after delivery with oral informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…7e11,15e20 One cohort study (n¼49) included the patients that sustained a dural puncture from diagnostic lumbar puncture. 21 For the cohort studies, four studies 7,10,17,18 were found to have some concerns for bias, five studies 8,9,11,14,16 were at high risk, and three studies 19e21 were at very high risk for bias when assessed by the ROBINS-E tool. The results of the risk of bias assessment is summarised in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%